1993
DOI: 10.1136/adc.69.2.181
|View full text |Cite
|
Sign up to set email alerts
|

How much wrapping do babies need at night?

Abstract: In a longitudinal, population based study, overnight temperature recordings were made in the bedrooms of 152 babies aged 3-18 weeks and the insulation provided by their bedclothing was assessed. Outdoor temperatures for the study nights were also available.Parents applied more insulation on colder nights with lower bedroom temperatures than on warmer nights (mean 8.5 tog at 15°C minimum bedroom temperature falling to 4-0 tog at 25°C). For a particular temperature they also applied 2 tog more insulation in wint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
2
37
0
Order By: Relevance
“…It has been assumed that the position at 4 weeks will be similar to that for the first 6 months of the child's life. The validity of this was shown in a separate study of 152 randomly selected children in Avon 8,13 which showed a slight decrease in prevalence of side sleeping between 1 and 3 months of age, with a corresponding rise in both supine and prone sleeping, but little change between 3 and 5 months of age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been assumed that the position at 4 weeks will be similar to that for the first 6 months of the child's life. The validity of this was shown in a separate study of 152 randomly selected children in Avon 8,13 which showed a slight decrease in prevalence of side sleeping between 1 and 3 months of age, with a corresponding rise in both supine and prone sleeping, but little change between 3 and 5 months of age.…”
Section: Methodsmentioning
confidence: 99%
“…As noted above, in a separate study of child care practices in a group of 152 Avon families randomly selected from the birth register in 1990 to 1991, no significant changes in routine sleeping position for infants were identified between 1 and 5 months of age, suggesting that the sleeping position at 4 weeks was a good proxy for usual practice throughout the first 6 months. 8,13 There are also the questions that must always arise in any study concerning the representative nature of the sample under scrutiny. The ALSPAC study achieved a high response rate, and covered over 85% of the eligible population.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the relation between the effective environmental temperature and the total thermal resistance of the bedding and clothing chosen by the parents (corrected for the proportion of surface area covered, as described previously) for the daytime sleep recordings.' 11 4 In the infants aged less than 3 months this decrease was less consistent and rarely more than 0 4°C, whereas for older infants the decrease was consistent and usually greater than 0 6°C. Figure 3 shows these changes with age for typical infants aged 30 and 184 days.…”
mentioning
confidence: 93%
“…A light clothing (2.5 tog) 16 was chosen to ease the nursing of the infant and the supervision of the sensors, and the room temperature was kept at 23°C (Ϯ.5°C) to obtain an environmental temperature close to the corresponding thermoneutral range. 17 The duvet covered the lower part of the body (up to midthorax).…”
Section: Study Conditionsmentioning
confidence: 99%